Tersilochinae (Hymenoptera: Ichneumonidae) of Papua New Guinea: genus Diaparsis Förster, part 2 . Species with notaulus - Khalaim, Andrey I.; Villemant, Claire (Zootaxa, 2021)
This second paper on the species of Diaparsis Förster occurring in Papua New Guinea comprises descriptions of ten new species and the second part of the key to the species. The following species are described as new to science: D. alpha sp. nov., D. beta sp. nov., D. delta sp. nov., D. epsilon sp. nov., D. eta sp. nov., D. gamma sp. nov., D. iota sp. nov., D. kappa sp. nov., D. theta sp. nov. and D. zeta sp. nov., raising the total number of currently known Diaparsis species in Papua New Guinea to nineteen.